2015
DOI: 10.3109/14767058.2015.1126242
|View full text |Cite
|
Sign up to set email alerts
|

Novel combined strategy of obstetric haemorrhage management during caesarean section using intrauterine balloon tamponade

Abstract: The proposed combined strategy of obstetric haemorrhage management represents a powerful tool for fertility-sparing treatment of this life-threatening condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In contrast, a separate study reported that none of the TEG variables was an independent predictor of massive transfusion or mortality . One study in a PPH setting was identified, and showed that TEG‐guided therapy reduced blood loss; blood loss (>2000 mL) and mean total blood loss occurred in a significantly lower percentage of patients . Further studies in a PPH setting are crucial, and, although recent guidelines do not recommend the use of viscoelastic hemostatic assays to predict PPH, they have highlighted their usefulness in major obstetric bleeding when used in conjunction with an agreed algorithm to guide blood transfusion …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a separate study reported that none of the TEG variables was an independent predictor of massive transfusion or mortality . One study in a PPH setting was identified, and showed that TEG‐guided therapy reduced blood loss; blood loss (>2000 mL) and mean total blood loss occurred in a significantly lower percentage of patients . Further studies in a PPH setting are crucial, and, although recent guidelines do not recommend the use of viscoelastic hemostatic assays to predict PPH, they have highlighted their usefulness in major obstetric bleeding when used in conjunction with an agreed algorithm to guide blood transfusion …”
Section: Resultsmentioning
confidence: 99%
“…Viscoelastic testing is a rapid, reliable technique that can be used to guide hemostatic therapy in bleeding patients, enabling individualized therapy by targeting the actual deficiencies of each patient. Guided hemostatic therapy can be of critical value in situations of high blood loss, such as major surgery (eg, cardiac surgery and liver transplantation), or in emergency control of bleeding due to trauma or postpartum hemorrhage (PPH) . Perioperative bleeding management guidelines recommend intervention algorithms based on viscoelastic coagulation monitoring, and highlight the predictive value of TEG results, particularly in an emergency setting .…”
Section: Introductionmentioning
confidence: 99%
“…Women who progressed to ≥4 units RBC had a FIBTEM A5 of 13 mm [interquartile range (IQR): 10–17] whereas those that did not progress had a FIBTEM A5 of 19 mm (17–23) (Collins et al , ). TEG clot strength measures, using an MA cut ‐off of 40 mm (kaolin TEG5000 MA) are also predictive of major obstetric haemorrhage: ROC AUC (95% CI) 0·9 (0·83–0·95) (Barinov et al , ). There are no published data on the role of Sonoclot for predicting progression of obstetric bleeding.…”
Section: Prediction Of Bleeding/coagulopathymentioning
confidence: 99%
“…An observational study compared standard care ( n = 29) with early surgical intervention, mechanical uterine pressure plus TEG‐guided transfusion ( n = 90) (Barinov et al , ). There was a statistically significant reduction in hysterectomy, total blood loss and FFP transfusion in the combined strategy group.…”
Section: Use Of Rotem/teg/sonoclot For Guiding Transfusion and Haemosmentioning
confidence: 99%
See 1 more Smart Citation